Anthropometric measurement of the lip-nose complex among young adults in Kuala Lumpur, Malaysia. - Durairajanayagam, Shamala (2011)
The lip-nose complex is an important aesthetic subunit of the mid and lower face. To date, there is no published data on lip-nose complex anthropometry for the Malaysian population. This cross sectional descriptive study aims to establish the norms of the lip-nose complex among Malaysian Malays, Chinese and Indians and to compare the transgender and transethnic variation between them. Seven parameters of the lip-nose complex namely mouth width, cupids bow width, columellar width, nasal width, lip height, columellar height and dome height were measured using standard anthropometric measurement tools. Three hundred sixteen-year-olds were randomly selected from three schools in Kuala Lumpur, with equal gender and ethnic distribution. Results obtained showed that all seven parameters the lip-nose complex in Malay, Chinese and Indian males were consistently larger than their respective female counterparts (p<0.05). The difference in lip-nose complex measurements for mouth width, nasal width, lip height and dome height were statistically different between Malays, Chinese and Indians. Mouth width and nasal width were widest among Malays. Lip height was highest amongst Indians. Dome height was highest amongst the Chinese. The cupids bow distance, columellar width and height showed minimal difference within the three races (p>0.05). Malays and Chinese differed in all parameters except cupids bow width. Malays and Indians only differed in mouth width and nasal width. Chinese and Indians differed in lip height and dome height. Malays and Chinese show differences in their lip-nose complex profile despite having originated from the East Asian continent. Malays and Indians differed in width measures, while the Chinese and Indians differed in height measures. The variation of anthropological measurements among the three ethnic groups reinforces the need to have individualized norms. These findings form a baseline for future studies that are age based which would then serve as an invaluable guide to the reconstructive surgeon especially when dealing with unilateral and bilateral cleft lip repairs.